Making Diagnostic of Gestational Trophoblastic Neoplasia : What, When, How to Treat and What to do Next ? - Anggraeni, Tricia D; Widyanti, Olivia (Indonesian Journal of Obstetrics and Gynecology, 2019)
A delay on diagnosing Gestational Trophoblastic Neoplasia (GTN) may cause increase of morbidity to the patient. The important things that OBGYN usually forgot is that GTN may develop not only from previous molar gestation (50-60%), but also from abortions or ectopic pregnancy (25-30%) and term or preterm deliveries (10-25%).1,2This can cause a delay on diagnosing that may increase the GTN score from low risk become high risk, such as this case, as follow.